Electric Power Losses Due to Transfer of Reactive Power in Electric Network and Ways of Their Limitation - E. G. Pоspelov; G. E. Pоspelov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2008)
Relationships have been obtained for determination of active power and energy losses due to transfer of reactive power in the lines of electric networks. The paper contains recommendations on decrease of these losses.